(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
This paper describes an experimental test campaign undertaken as part of the USI funded Control Co-Design of Heterogeneous Arrays of Wave Energy Converters in the Wide Wave Basin at Queen’s Marine Laboratory. The overall aim of this project is the development and experimental validation of control strategies for arrays of wave energy converters of different size or shape. This paper focusses on the validation of the physical models and the experimental design, highlighting the levels of accuracy required to identify array interaction. Earlier studies have highlighted deficiencies in array optimization studies due to the spatial variation in wave height across the test facility and variations among individual WEC models build to the same specification. This campaign draws from earlier experience of similar tests and implements improvements to the drive trains, like double air bearings to minimise friction even during significant loading in surge direction and linear motors to provide versatile and programmable PTO modelling capability. Models will be build in identical pairs, such that each experiment can employ four WEC models with two different characteristics. Experiments will be repeated after swapping each identical pair of models to assess the effect of model variation. Array layouts will also be tested at different locations in the tank to asses wave climate homogeneity. Results will provide a clear understanding of the limitations for this type of experimental testing and inform future test campaigns, which are planned to trial novel control algorithms specifically developed for heterogeneous wave energy converter arrays.